The Impact of Inquiry based Learning and Explicit Instruction of the Nature of Science on Students’ Views of the Nature of Science - HAWASH, WAEL ABOU (2017)
Education of science has increasingly attracted new and novel approaches. Recent studies have sought to introduce strategies and methods for teaching science that will significantly enhance learners’ capacity to appreciate science. Educators are now at a better position to explore and experiment with new pedagogic approaches. Inquiry-based learning approaches and explicit instruction of the nature of science are contemporary topics in pedagogy. The purpose of this research is to investigate the impact of the inquiry-based and explicit instruction of the Nature of Science on students’ views of the nature of science. It provides insights on how inquiry based learning and explicit instruction of the NOS can be applied in the context of the UAE to improve learners’ views of NOS. A quantitative research method is used and a quasi-experimental approach is adopted i.e. pre and post tests involving 3 groups apart from the control group. The teachers of the three groups are chosen using the instrument to have adequate views of the nature of science. The 3 groups are taught using science textbooks aligned with the next generation science standards (NGSS). All of the students of the school are Emiratis and the teachers are multinational and they needed to have teaching license of their area of specialty. A pretest was conducted to all groups. Similarly, all groups were taught the same science lesson i.e. same scientific concepts however as the research suggested with different techniques namely inquiry based, explicit instruction, and inquiry and explicit while the control group through direct instruction rote learning. The findings of this study have shown that the combination of both instructional approaches, inquiry based and explicit teaching of the NOS, brings the best of both to the classroom leading to significantly improved views of NOS (t=-8.004, df = 20, p = .000). This study recommends further investigation with and combination of both explicit and inquiry-based instruction approaches in teaching science. Science teachers should aim towards determining the optimal mix of both approaches that will results in the best NOS outcomes for their student.